Particulate Matter-Monitoring During End-Milling Under Different Cooling-Lubrication Strategies - Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Husshini, Nur Husnina Najeah; Mohammad Shah All Hafiz, Mohd Shahrim; W. Mohamad, W Noor Fatihah; Ghani, Jaharah Abdul; Haron, Che Hassan (Tamkang University Press, 2021)
Many lubrication strategies have been applied in cutting processes. The main purpose is to reduce heat generated and to lower friction on the cutting tool thus improving the surface quality of the workpiece. However, the quality of indoor air has become a major health and safety issue. This study explains the effects of cooling, lubrication strategies and cutting parameters on particulate matter emission. The experiments involved the use of TiCN CVD coated carbide with varying cutting speeds (Vc), feed rates (fz), and cooling-lubrication strategies (dry, chilled air, chilled MQL, MQL, flood-coolant and pulsating lubrication) for both Aluminium alloy 6061 and Inconel 718. Design of experiment and analysis of variance (ANOVA) were used to examine the effects of the input parameters on the PM2.5 value. Based on ANOVA, it was found that the chilled MQL and MQL exhibited high PM2.5 readings, while the other coolant strategies yielded results which were within an acceptable exposure limit.